Chloride Influx of Anion Exchanger 2 Was Modulated by Calcium-Dependent Spinophilin in Submandibular Glands - Lee, Dongun; Lee, Sang A.; Shin, Dong M.; Hong, Jeong H. (Frontiers in Physiology, 2018)
Secretory glands including salivary glands by many hormonal inputs produce and secrete biological ﬂuids determined by variety of ion transporters. Spinophilin is a multifunctional scaffolding protein, which involved in receptor signaling and regulation of anion exchangers AE2 activity. We found that spinophilin expressed in salivary glands. The role of salivary spinophilin on the modulation of chloride/bicarbonate exchange remains unknown. The spinophilin enhanced AE2 activity and associated with a STE20/SPS1-related kinase and showed an additive effect on the modulation of the activity of AE2. The cholinergic stimulation and subsequent intracellular Ca2+ increase was required for the interaction with AE2 and spinophilin and abrogated the enhanced effect of spinophilin on Cl− transporting activity. Ductal chloride/bicarbonate exchange activity was increased in pretreatment with carbachol. The CaMKII inhibitor KN-93 suppressed the chloride/bicarbonate exchange activity of ducts, suggesting that CaMKII was required for ductal chloride/bicarbonate exchange activity. Additionally, microtubule destabilization by nocodazole attenuated the interaction of AE2 and spinophilin and almost abolished the ductal chloride/bicarbonate exchange activity. The treatment of siRNA-spinophilin on the isolated salivary ducts also reduced the ductal chloride/bicarbonate exchange activity. Therefore, role of salivary spinophilin on AE2 may facilitate the Cl− influx from basolateral in salivary glands in response to cholinergic inputs.